1984
DOI: 10.1128/mcb.4.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Chinese hamster-human hybrid cell line with increased system L amino acid transport activity.

Abstract: We have studied leucine transport in several Chinese hamster-human hybrid cell lines obtained by fusion of a temperature-sensitive line of Chinese hamster ovary cells, tsO25C1, and normal human leukocytes. A hybrid cell line exhibiting a twofold increase in L-leucine uptake over that in the parental cell line was found. This hybrid cell line, 158CnpT-1, was temperature resistant, whereas the parental Chinese hamster ovary mutant, tsO25C1, contained a temperature-sensitive leucyl-tRNA synthetase mutation. An ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…Suppression of the temperature-sensitive phenotype with cell fusions to human leukocytes has localized the tRNN eu synthase gene to chromosome 5 and the gene encoding the System L carrier protein to chromosome 20 (Lobaton, Moreno & Oxender, 1984). These studies are in agreement with the postulate of Moore et al (1977) who suggested that the regulation of system L is dependent on the concentration of charged tRNA le" molecules.…”
Section: System a Regulation--a Brief Summarysupporting
confidence: 77%
“…Suppression of the temperature-sensitive phenotype with cell fusions to human leukocytes has localized the tRNN eu synthase gene to chromosome 5 and the gene encoding the System L carrier protein to chromosome 20 (Lobaton, Moreno & Oxender, 1984). These studies are in agreement with the postulate of Moore et al (1977) who suggested that the regulation of system L is dependent on the concentration of charged tRNA le" molecules.…”
Section: System a Regulation--a Brief Summarysupporting
confidence: 77%
“…Using a hybrid between CHO ts025C1 containing a temperature-sensitive leucyl t-RNA synthetase and normal human leukocytes, it has been possible to identify a gene on human chromosome 20 that codes for a component that produces increased L-system activity in the hybrid [30]. The hybrid has the maximum derepressed level of the L system as exhibited at moderate nonpermissive temperatures by the ts parent and is not further derepressible.…”
Section: Oxender Personal Communication]mentioning
confidence: 98%
“…Transport of alanine in the absence of Na + is subtracted from that obtained with alanine in the presence of saturation amount of Me?lIB [30,48,51]. It is recognized by these investigators that this assay procedure might include other MeAIB resistant, Na+-dependent transport systems.…”
Section: A Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of leucine transport proteins in E. coli may also be involved in regulating leucyl-tRNA synthetase because a mutant with an apparent deficiency in leucine transport displays a 3-fold elevation in enzyme level (8). Several lines of evidence also suggest a role for leucyl-tRNA synthetase in regulating leucine transport in Chinese hamster ovary cells (9)(10)(11)(12)(13). We report here that sequences in the potential nucleotide-binding domain of leucyl-tRNA synthetase display a high degree of sequence and structural similarity to the carboxyl-terminal domain of the leucine-specific binding protein.…”
mentioning
confidence: 70%